THE SECONDARY ANTIBODY TITER AGAINST STREPTOCOCCUS SUIS VACCINE WITH DIFFERENT ADJUVANTS IN RAT - Rumapea, Sumanna; Mahardika, I Gusti Ngurah Kade; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2022)
Streptococcus suis is a pathogenic bacteria which can cause an infection in animals nor humans. This study aimed to determine the difference in secondary antibody from the administration of S. suis vaccine with different adjuvants. This research is experimental with complete randomized design. Total of 15 rats was divided into 3 groups. Each groups was given S. suis vaccine with adjuvant  Montanide TM ISA 78; Montanide TM ISA 201; Montanide TM Gel 01 by IM. The serum were taken from sinus orbitalis on the week 0 (pravacination), 1 st week, 2 nd week and 3 rd week after booster. The secondary antibody titer were measured by indirect ELISA method. Data were analyzed using analysis of variance, then continued by LSD test. The result showed that S. suis vaccine with different  adjuvants had a significant effect (P<0,05). S. S. suis vaccine with Montanide TM ISA 78 (w/o) produced the highest secondary antibody (OD = 0,331), then S. suis vaccine with Montanide TM Gel 01 (OD = 0,256). The lowest titer antibody was produced by S. suis vaccine with  Montanide TM ISA 201 (w/o/w) adjuvant (OD = 0,208). From the results of this study, it can be concluded that the S.suis vaccine formulation with Montanide TM ISA 78 (w/o) is the best vaccine formulation in production of secondary antibody.